Identification of Employee Management in MSMEs - Aloysius Dhimas Trikurnian; Januari Ayu Fridayani (Soegijapranata Catholic University, 2024)
MSMEs (micro, small, and medium enterprises) are a crucial component of global economic expansion and exert a substantial influence on employment creation worldwide. Proper staff management is a critical determinant of success and sustainability for MSMEs in their operational endeavors. This study examines personnel management techniques and practices employed by MSMEs in the tourist sector focusing on CV OBKA Mandiri as a case study. The findings of this study demonstrate that CV OBKA Mandiri employs a distinctive method in managing their workforce. The organization places significant emphasis on fostering a culture of collaboration and teamwork among its workforce. The employees are seen as integral members of the firm, with a strong emphasis placed on the value of teamwork. The belief in the significance of mutual success is held by individuals. This research also emphasizes the significance of employee engagement and motivation in the management of employees in MSMEs. CV OBKA Mandiri recognizes the correlation between employee motivation and engagement in their work and the subsequent positive impact on the firm. Furthermore, the findings of this study emphasize the significance of staff training and development within MSMEs. The firm has undertaken significant measures in this context, offering useful insights into the implementation of human resource management. This study offers significant contributions to the understanding of staff management within the context of MSMEs. The findings can serve as a valuable resource for MSMEs in addressing unique obstacles such as the Covid-19 pandemic and its consequences.